2011
DOI: 10.1007/s11356-011-0605-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk posed by chlorinated organic compounds in Abu Qir Bay, East Alexandria, Egypt

Abstract: With the help of a SLERA, it was possible to indicate which class of chlorinated organic compounds is of highest concern to assess and to improve the environmental quality of the bay. Monitoring of organochlorines and chlorpyrifos would be needed to control the future trend of pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In the last decade they are still being identified; they have been found in ten IMF from India, in concentrations that fluctuate between 0.04 -335.87 μg/kg fat basis, among which β-HCH, α-endosulphan, malathion, dimetoate, dieldrin and aldrin were found present in most of the IMF [6]. Recently the content of these derivates was measured in soils of the La Lorraine Region in France and the highest content was presented by β-HCH with a value of 0.64 ± 0.15 μg/kg [4]. Their presence has also been estimated in the Bay of Abu Qir in Egypt [2] and their presence was reported along with other organochlorine compounds in sediments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade they are still being identified; they have been found in ten IMF from India, in concentrations that fluctuate between 0.04 -335.87 μg/kg fat basis, among which β-HCH, α-endosulphan, malathion, dimetoate, dieldrin and aldrin were found present in most of the IMF [6]. Recently the content of these derivates was measured in soils of the La Lorraine Region in France and the highest content was presented by β-HCH with a value of 0.64 ± 0.15 μg/kg [4]. Their presence has also been estimated in the Bay of Abu Qir in Egypt [2] and their presence was reported along with other organochlorine compounds in sediments.…”
Section: Resultsmentioning
confidence: 99%
“…Although numerous legislations have prohibited its use in many countries, its stability makes it persistent and its derivate DDE has been qualified as highly toxic. In addition to the content of the family of the HCH, heptachlor, heptachlor epoxide, hexachlorobenzene, endosulphan, aldrin and dieldrin, both in sediments of Abu Qir Bay in Egypt and in soils of La Lorraine, Ʃ-DDT was calculated in 27 μg/kg in the Egyptian zone and in soils of the French region studied at 0.2 and 2.3 μg/kg [2] [4].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish and shellfish : Mussels from Abu Qir Bay contained several OCPs, with DDT concentrations up to 31 µ g/g dw (Table 1), but a risk assessment showed no expected adverse effects on people through mussel consumption [47]. A study of fish in Assiut city region found higher levels of various OCPs in catfish compared to tilapia, though all were below recommended MRLs (Table 2…”
Section: Ocp Contamination Of Foods In African Countriesmentioning
confidence: 99%
“…For some other AOPs directly utilizing the strong oxidant, they could lead to the complete mineralization of the pollutants and convert them into environmental-friendly compounds such as CO 2 and H 2 O [10]. It is still noteworthy that some drawbacks hinder its wide practical application such as the generation of carcinogenic by-products (chlorite and chlorate) when using chloride in drinking water disinfection [11,12], and the high cost and harmful by-products (e.g. bromate) of the ozonation process [13].…”
Section: Introductionmentioning
confidence: 99%